P1645VITAMIN K DEPENDENT PROTEINS AFTER KIDNEY TRANSPLANTATION: RESULTS FROM PROSPECTIVE STUDY. (6th June 2020) - Fusaro, Maria; Khairallah, Pascale; Aghi, Andrea; Plebani, Mario; Zaninotto, Martina; Cosma, Chiara; Aponte Farias, Maria A; Cortez, Natalia E; Tripepi, Giovanni Luigi; Nickolas, Thomas
Abstract: Background and Aims: Two Vitamin K-dependent proteins (VDKPs) link bone and vasculature in CKD-MBD: Bone Gla Protein (BGP) and Matrix Gla Protein (MGP). In ESKD, Vitamin K deficiency is highly prevalent and leads to increased levels of inactive VKDPs (undercaboxylated (ucBGP and dephosphorylated (dp)-uMGP), which are linked to greater risk of fractures and severity of vascular calcification. We hypothesized that kidney transplantation (KT) would improve Vitamin K status and lower levels of inactive VKDPs. Method: Between 2014-2017, we conducted a study in 34 patients to assess changes in VKDPs during the 1st year of KT. In a specialized lab we determined VKDPs pre- and 1-year post-KT: total BGP, uc BGP, total MGP, and dp-uc MGP. We determined the prevalence of Vitamin K deficiency based on levels of uc BGP and dp-uc MGP. Results: Our cohort had a mean +/- SD age of 48+/-14 years, 32% were female and 97% were Caucasian. 1 year post-KT, there was a decrease in the levels of all VKDPs and the prevalence of Vitamin K deficiency (Table 1 and Figure 1 ). Patients with greatest severity of Vitamin K deficiency pre-KT had the largest decreases of inactive VDKPs post-KT. Conclusion: KT was associated with improvement in Vitamin K status as manifested by decreased levels of inactive VKDPs. These are the first prospective data on VKDPs in CKD patients pre- and post-KT. Studies are needed to assess the impact of improvement in VKDP status after KT on CKD-MBD outcomes.